Risk factors of neonatal tetanus in Wenzhou, China: a case-control study - Zu-Mu Zhou; Hong-Ying Shi; Yi Xu; Cai-Song Hu; Xiao-Ming Zhang; Li-Na Zhao; Zuo-Kai Xie (World Health Organization Regional Office for the Western Pacific, 2015)
Introduction: Neonatal tetanus is a major cause of neonatal mortality in many developing countries and remains a major public health problem. This study aimed to determine risk factors associated with neonatal tetanus in Wenzhou, China. Methodology: Medical records of neonatal tetanus cases from 17 hospitals over a 13-year period (2000-2012) were reviewed for potential risk factors. Controls were selected from neonates with diseases other than tetanus who were admitted to the same facility during the same period. The potential risk factors of the neonatal tetanus group were compared with the control group using univariate analysis and an unconditional logistic regression model. Results: A total of 246 neonates with tetanus and 257 controls were included in this study. Univariate analysis showed that the odds of having untrained birth attendants, home delivery, an unsterile method of delivery and being a migrant to Wenzhou were significantly different between the two groups (P < 0.001). Logistic regression analysis revealed that having an untrained birth attendant, home delivery and an unsterile method of delivery were significantly higher in the tetanus group than the control group (odds ratio: 1371.0; 95% confidence interval: 206.0, 9123.5). Conclusion: This study identified that the main risks of neonatal tetanus in cases from Wenzhou were having an untrained birth attendant, home delivery and an unsterile method of delivery. Preventive measures directed to these risk factors may reduce the occurrence of neonatal tetanus in the studied area.